Editorial: Introduction to the Special Issue - Goularas, Gökçe Bayındır (Border Crossing, 2018)
This special issue of the Border Crossing Journal seeks to bring together a collection of papers presented during the second international conference “International Migration in the 21st century”, organized in October 2017 by the Research Center of Global Education and Culture (KEKAM) of Yeditepe University in Istanbul.